A materials perspective on radiative cooling structures for buildings. (1st September 2020) - Li, Wenxin; Li, Yanru; Shah, Kwok Wei
Abstract: As a promising climate change mitigation technology, radiative cooling presents an economical and environmental-friendly approach to alleviate cities from overheating and urban heat island. Based on the fundamental theory, this study comprehensively reviews the materials composition and nano/microstructures underlying the radiative cooling technology. The study summarizes the primary six properties of the selective emitting material, reflecting material, back-mirror material, matrix material, insulation material and dynamic switching material, in terms of their morphologies, substrates, properties, and performances. The configuration of radiative cooling systems mostly follows the two essential designs, namely "multi-layered structures" composed of multiple continuous nano/micro-layers or "nano/micro-particle structures" consisting of discrete nano/microparticles or a combination of both. Cooling potential and end-applications on buildings were reviewed, including cool roofs, PV cooling and water cooling. At the end of this review, we present our recommendations on the combining "multilayer" and "nanostructure" designs for better design radiative cooling composites from a materialistic perspective. Unlike previous studies, our review provides a unique overview of nanomaterials and composite structures, leading to better design configuration and optimisation of radiative cooling end-applications.